Akar dan Solusi Menghadapi Krisis Moral di Era Globalisasi: Analisis Pemikiran Ibnu Khaldun - Maman Maman; Abd. Rahman Hamid; Muhammad Akmansyah; Sudarman Sudarman (Jurnal Dirosah Islamiyah, 2026)
The era of globalization is characterized by the advancement of science and technology (e.g., epitome). A problem that frequently arises amidst the development of science and technology is the moral crisis. Furthermore, there is a moral decline in various sectors, both in society and government. This moral problem, which has spread across various dimensions, is one of the topics that needs immediate attention and constitutes a serious concern that must be addressed and resolved immediately. The anticipated goal of this research is to analyze Ibn Khaldun's thought in finding solutions to the moral crisis in the era of globalization. This research is desk research. Through this research study, at least several important points have been reached. Ibn Khaldun's ideas can be used as a basis for analysis to provide solutions to confront the ethical crisis in the current era of globalization, provide new knowledge, and explain the roots of problems that occur in people's lives. This thinking not only enriches scientific knowledge but also offers and explores a study to answer the challenges of life today. In general, Ibn Khaldun's method of reasoning in proposing solutions to various societal problems is grounded in reality, leading to the emergence of new knowledge that can be directly addressed in addressing various societal problems, particularly those related to solutions to moral crises, and whose practical benefits can be tangibly demonstrated.